Double Negative B Cell Is Associated With Renal Impairment in Systemic Lupus Erythematosus and Acts as a Marker for Nephritis Remission - You, Xujie; Zhang, Ruijun; Shao, Miao; He, Jing; Chen, Jiali; Liu, Jiajia; Zhang, Xia; Liu, Xu; Jia, Rulin; Sun, Xiaolin; Li, Zhanguo (Frontiers in Medicine, 2020)
Objective: Recent studies on double negative B cells (DN B cells) suggested that they have potential pathogenic roles in systemic lupus erythematosus (SLE). This study aimed to determine the circulating DN B cells in SLE patients and analyzed the clinical significance of this cell subset. Methods: Fifty-seven SLE patients and fifty healthy controls (HCs) were recruited in this study. Among the 57 SLE patients, 25 had lupus nephritis (LN). All patients were followed up for 24 weeks. Peripheral B cell subsets were analyzed by flow cytometry. Results: DN B cells were significantly elevated in the SLE patients, especially in the patients with LN (p < 0.01). DN B showed a positive correlation with 24-h urine protein excretion (24 h-UPE) levels (r = 0.444, p = 0.034) in LN patients, and inversely correlated with evaluated glomerular filtration rate (eGFR) (r = −0.351, p = 0.011). DN B cells had a positive correlation with plasma cells (r = 0.484, p < 0.001) and memory B cells (r = 0.703, p < 0.001). After treatment, decreased DN B cells were associated with LN alleviation (p = 0.002). In the follow-up, the remission rate of LN patients with decreased DN B cells was significantly higher than LN patients with increased DN B cells (83.33 vs. 25.00%, p = 0.030) at week 24. Conclusions: This study suggests that the peripheral DN B cells are positively correlated with the severity of renal damage in LN patients and may potentially be used as a prognostic marker in LN.